THE PROSPECT OF PARTICULARLY SENSITIVE SEA AREA (PSSA) DESIGNATION IN LOMBOK STRAIT - Angela Jessica Desmonda; Idris (International Law Department, Faculty of Law Universitas Padjadjaran, 2020)
AbstractInternational Law, specifically UNCLOS 1982, MARPOL 73/78, and SOLAS 1974 give mandates to every State to carry out protection and prevention of marine pollution. As one form of protection and prevention pollution is establishing a Particularly Sensitive Sea Area (PSSA). Since 2016, the Indonesian Government has submitted a proposal to designate the Lombok Strait as one of the PSSA. This study aims to analyze and provide an understanding of the prospects for the establishment of PSSA in the Lombok Strait including the Gili Islands and Nusa Penida Island after the approval of the Traffic Separation Scheme (TSS) in 2019 based on International Law.This study uses a juridical-normative approach with descriptive analytical research to describe and analyze the international legal instruments used. The research data were obtained from the results of library research and interviews with related institutions such as the Ministry of Foreign Affairs and the Ministry of Transportation of the Republic of Indonesia. Data processing conducted by qualitative analysis methods. This study concludes that the specific PSSA arrangements are governed by the IMO Resolution A.982 (24) related to the PSSA Guidelines as PSSA is not explicitly regulated in UNCLOS 1982. The Lombok Strait is highly prospective to be established as a PSSA as the Lombok Strait has fulfilled the criteria of the IMO accompanied by the mandate of protection and prevention of the marine environment from UNCLOS 1982, MARPOL 73/78 and SOLAS 1974.In 2019, the designation of TSS in Lombok Strait was approved so that discussions related to PSSA can continue. However, The PSSA discussed at the IMO session requires the approval of other countries that enjoy the rights of passage through the Lombok Strait. Accordingly, the attribute section of the PSSA determination proposal in the Lombok Strait needs to be improved to convince that the Lombok Strait does have the urgency to be established as a PSSA.Keywords: Particularly Sensitive Sea Area, Lombok Strait, International Maritime Organization AbstrakHukum Internasional, khususnya UNCLOS 1982, MARPOL 73/78, dan SOLAS 1974 memberikan mandate kepada setiap negara untuk melakukan perlindungan dan pencegahan pencemaran di laut. Salah satu perwujudannya yaitu dengan membentuk Kawasan Perairan Sensitif/Particularly Sensitive Sea Area (PSSA). Sejak tahun 2016, pemerintah Indonesia telah mengajukan proposal penunjukan Selat Lombok sebagai PSSA. Penelitian ini bertujuan untuk menganalisa dan memberi pemahaman terkait prospek penetapan Kawasan Perairan Sensitif (PSSA) di Selat Lombok termasuk Pulau Gili dan Pulau Nusa Penida pasca ditetapkannya Skema Pemisah Lalu Lintas (TSS) pada tahun 2019 berdasarkan Hukum Internasional. Penelitian ini menggunakan pendekatan yuridis-normatif dengan jenis riset deskriptif analitis untuk menggambarkan dan menganalisis instrumen-instrumen hukum internasional yang digunakan. Data penelitian diperoleh dari hasil penelitian kepustakaan dan wawancara dengan lembaga terkait seperti Kementerian Luar Negeri dan Kementerian Perhubungan Republik Indonesia. Pengolahan data dilakukan dengan metode analisis kualitatif. Penelitian ini menyimpulkan bahwa pengaturan PSSA secara spesifik dimuat di dalam Resolusi IMO A.982 (24) terkait Pedoman Identifikasi dan Penetapan PSSA. Hal ini merupakan aturan lanjutan dikarenakan PSSA tidak diatur secara eksplisit di dalam UNCLOS 1982. Tahun 2019 penetapan Skema Pemisah Lalu Lintas TSS sebagai salah satu syarat pembentukan PSSA di Selat Lombok telah disetujui sehingga pembahasan terkait PSSA dapat terus dilanjutkan. Namun masih diperlukan persetujuan negara-negara lain yang memiliki hak melewati Selat Lombok. Oleh karenanya, perlu penguatan proposal khususnya terkait bagian atribusi untuk lebih meyakinkan urgensi penetapan Selat Lombok sebagai PSSA. Kata Kunci: Kawasan Perairan Sensitif, Selat Lombok, Organisasi Maritim Internasional